The Effectiveness of Policy Implementation of Rice Land Conversion Control to Support National Food Security in KarawangRegency West Java Province - Fahmi Ardiansyah; Muhadam Labolo; Tjahjo Suprajogo; Eko Budi Santoso (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Rice field conversion has become a critical governance issue in regions where food security objectives intersect with industrial and urban expansion. This study analyzes the effectiveness of rice field conversion control policy in supporting national food security in Karawang Regency, West Java Province, Indonesia. Karawang is a strategic rice-producing region, yet it also functions as a major industrial growth area, creating persistent pressure on productive paddy fields. Using a qualitative case study design, data were collected from 35 informants representing policy makers, policy implementers, farmers, academics, journalists, and community actors through semi-structured interviews, field observation, and document review. The data were analyzed through thematic analysis using five dimensions of policy implementation effectiveness: appropriate policy, appropriate implementation, appropriate target, appropriate environment, and appropriate process. The analysis was expanded by examining compensation adequacy and policy synchronization as emerging empirical dimensions. The findings show that the policy has a strong formal foundation and is relevant to agricultural land protection, but its implementation remains only partially effective. Limited public understanding of LP2B, uneven field supervision, weak target achievement, insufficient farmer incentives, and poor alignment between agricultural protection and industrial development continue to constrain policy effectiveness. This study contributes to policy implementation literature by positioning compensation adequacy and policy synchronization as central dimensions of land-use governance in rapidly industrializing agricultural regions. Practically, the study recommends stronger LP2B socialization, integrated inter-agency monitoring, fairer farmer support schemes, and agro-industrial policy alignment to protect productive rice fields and strengthen sustainable food security.